The effects of REG4 expression on chemoresistance of ovarian cancer - Li-Wei Xiang; Hang Xue; Min-Wen Ha; Da-Yong Yu; Li-Jun Xiao; Hua-Chuan Zheng (Taylor & Francis Group, 2022)
AbstractAlthough ovarian cancer usually responds well to platinum- and taxane-based first-line chemotherapy, most patients develop recurrence and chemoresistance. Regenerating gene 4 (REG4) is a secretory protein involved in cell differentiation and proliferation. We found higher REG4 expression in ovarian cancer than in normal tissues (p < .05). Regenerating gene 4 expression was negatively associated with overall, progression-free or post-progression survival rates of patients with ovarian cancer receiving platinum or paclitaxel treatment (p < .05) according to a Kaplan-Meier plotter. Regenerating gene 4 overexpression resulted in either cisplatin or paclitaxel resistance, and apoptosis resistance in CAOV3 ovarian cancer cells (p < .05). REG4-transfected ovarian cancer cells showed stronger migration and invasion treated with cisplatin or paclitaxel (p < .05). Additionally, cisplatin or paclitaxel exposure led to the overexpression of phosphorylated phosphoinositide 3-kinase (p-PI3K), p-Akt, phosphorylated mammalian target of rapamycin (p-mTOR), glutathione S-transferase-π, survivin, and B-cell lymphoma 2 in REG4 transfectants compared with control cells (p < .05). These findings suggested that REG4 expression was up-regulated in ovarian cancer, and associated with poor survival and chemotherapy resistance. REG4 promoted the occurrence, development, and chemotherapy resistance of ovarian cancer by regulating cell proliferation, apoptosis, migration, and invasion, and PI3K/Akt/m-TOR signalling pathways. IMPACT STATEMENTWhat is already known on this subject? REG4 mRNA expression is up-regulated in many digestive cancers. High REG4 expression was associated with an adverse prognosis, high tumour and nodal stages, poor differentiation, and hepatic and peritoneal metastases of digestive cancers. REG4 expression conferred cancer cells with increased resistance to chemoradiotherapy, especially 5-FU-based treatment, by activating the MAPK/Erk/Bim signalling pathway.What do the results of this study add? REG4 was highly expressed in ovarian cancer. The expression of p-PI3K, p-AKT, p-mTOR, GST-π, survivin, and Bcl-2 was increased in REG4-overexpressing cells. High REG4 expression was significantly associated with inferior OS, PFS, and PPS rates in patients with ovarian cancer receiving platinum chemotherapy. REG4 mediated cisplatin and paclitaxel resistance in CAOV3 ovarian cancer cells. The percentage of apoptotic cells was markedly lower in REG4-transfected compared to mock-transfected cells after cisplatin or paclitaxel treatment.What are the implications of these findings for clinical practice and/or further research? This study aimed to evaluate the prognostic significance of REG4 expression in ovarian cancer treated with platinum and paclitaxel, to explore REG4 chemoresistance mechanisms to platinum and paclitaxel, and to provide a scientific experimental basis for the clinical treatment and outcome evaluation of ovarian cancer. In order to provide comprehensive clinical treatment of ovarian cancer, it is helpful to improve our understanding of multi-drug resistance and identify new cancer diagnostic biomarkers.